A Novel Sum and Difference Phase-comparison Algorithm for Uniform Circular Phase Array Radar. Issue 3 (March 2021) - Dai, Zheng; Gu, Hong; Su, Weimin
Abstract: Phase-comparison of sum and difference angle measurement technique can be simply applied to uniform linear phased array radar. In contrast, it is not so simple for uniform circular phased array radar because the relation between ratio of difference to sum and target azimuth angle is complex. In this letter, we present this problem; based on derivation and approximate treatment, we propose an algorithm to solve this problem. The proposed algorithm is easy to implement and has good angle measurement performance. Computer simulations are shown to verify the efficacy of the proposed method.